Diabetic Ketoacidosis at Onset of Type 1 Diabetes: Rates and Risk Factors Today to 15 Years Ago - Shana Rose Mencher MD; Graeme Frank MD; Joanna Fishbein MPH (SAGE Publishing, 2019)
Diabetic ketoacidosis (DKA) is a serious, potentially lethal complication of type 1 diabetes mellitus that may be present at diagnosis. The aim of this study was to determine factors associated with presentation in DKA in new-onset youth and compare the rate of DKA and risk factors to a similar study 15 years prior. This study was a retrospective chart review of newly diagnosed patients with type 1 diabetes mellitus from 2010 to 2013. Of the 276 patients, 29% presented in DKA, compared with 38% 15 years prior ( P < .002). Those with Medicaid, those misdiagnosed at initial encounter, and those not evaluated by a pediatrician initially were more likely to present in DKA ( P = .002, P = .002, P < .001, respectively). The diagnosis of diabetes was not elicited in one third of patients who ultimately presented in DKA. Pediatricians should be reeducated to ask about polyuria and polydipsia in routine encounters. Furthermore, public awareness initiatives are needed to reduce late presentation in DKA.